The Blasingame method considering the effect of inter-well interference in a circular homogeneous closed reservoir - Du, Pengfei; Wang, Qi; Zhang, Jing; Wang, Yanwei; Wang, Dong; Han, Yi; Liu, Pengcheng (Frontiers in Energy Research, 2024)
The Blasingame method serve as a valuable tool for analyzing the diminishing production challenge in the presence of variable bottomhole pressure and diverse production conditions. It is essential to highlight that the Blasingame method views the closed reservoir as the outer boundary condition for its model. This paper introduces the concept of the equivalent well control radius and formulates the Blasingame method based on the fluid flow characteristics inherent in twin-well production, taking into account the influence of inter-well interference. This study provides an in-depth analysis of production variations in reservoirs with inter-well interference by examining Blasingame type-curves' definitions of the dimensionless parameters.Additionally, it investigates key factors impacting production, including neighboring wells' production, well distance, and the opening time of neighboring wells: variations in all three parameters lead to different levels of interference between wells, which manifests itself in the regularised production integral derivative curve as different lengths and heights of convexity. To validate the reliability of this method, numerical simulations employing orthogonality are conducted.The results of these simulations offer theoretical support for the precise evaluation of reservoirs facing similar challenges.